Stress Abolishes the Effect of Previous Chronic Ethanol Consumption on Drug Place Preference and on the Mesocorticolimbic Brain Pathway - Daniel Moreira‐Silva; Gessynger Morais‐Silva; Juliana Fernandes‐Santos; Cleopatra S. Planeta; Marcelo Tadeu Marin (2014)
Background Conditioned place preference ( CPP ) to ethanol (EtOH) is an important addiction‐related alteration thought to be mediated by changed neurotransmission in the mesocorticolimbic brain pathway. Stress is a factor of major importance for the initiation, maintenance, and reinstatement of drug abuse and modulates the neurochemical outcomes of drugs. Thus, the aim of this study was to investigate the effects of concomitant exposure to chronic EtOH and stress on CPP to this drug and alterations of dopaminergic and serotonergic neurotransmission in mice. Methods Male Swiss mice were chronically treated with EtOH via a liquid diet and were exposed to forced swimming stress. After treatment, animals were evaluated for conditioning, extinction, and reinstatement of CPP to EtOH. Also, mice exposed to the same treatment protocol had their prefrontal cortex ( PFC ), nucleus accumbens ( NA c), and amygdala dissected for the quantitation of dopamine, serotonin, and their metabolites content. Results Data showed that previous chronic exposure to EtOH potentiated EtOH conditioning and increased dopaminergic turnover in PFC . Exposure to stress potentiated EtOH conditioning and decreased dopaminergic turnover in the NA c. However, animals exposed to both chronic EtOH and stress did not display alterations of CPP and showed an elevated content of dopamine in amygdala. No treatment yielded serotonergic changes. Conclusions The present study indicates that previous EtOH consumption as well as stress exposure induces increased EtOH conditioning, which can be related to dopaminergic alterations in the PFC or NA c. Interestingly, concomitant exposure to both stimuli abolished each other's effect on conditioning and PFC or NA c alterations. This protective outcome can be related to the dopaminergic increase in the amygdala.